Legal Enforcement by the Police against Child of Criminal Doer of a Traffic Accident Who Caused Death (Case Study in Traffic Accident of Police Traffic Unit of Cirebon City Police Juridiction) - Anton Susanto; Ira Alia Maerani; Maryanto Maryanto (Jurnal Daulat Hukum, 2020)
The problems of this study were 1) the process of resolving the crime of traffic accident committed by a child which causing death in Jurisdiction Police Cirebon, 2) the difference between the completion of the crime of traffic accident by a child which causing death by perpetrators of adults in Police Cirebon City? 3) consideration of the law by the police in the Cirebon City Police enforcement of laws against the crime of traffic accident causing death committed by a child.The method used is research that combines Juridical and Empirical. The source of research data derived from primary data and secondary data obtained by collecting documents and interviewing criminal cases with informants.Based on research findings conducted by researchers regarding law enforcement in case of a traffic accident causing death committed by minors resolved with the criminal justice process method to process outside the criminal justice and restorative justice approach that is Diversion. Based on Act No. 11 of 2012 on the Criminal Justice System Child involvement of multiple stakeholders in the settlement became a mandatory provision. Constraints law enforcement officials in the execution of diversion itself is the factor of legal, officials law enforcement factors, community factors and factors of facilities and infrastructure.Keywords: Law Enforcement; Police; Accident; Traffic; Child.